A New Approach for Determining Hyperparameters in Artificial Neural Networks: Enhanced Black Hole Optimization Algorithm - Bilen, Mehmet (Journal of Multidisciplinary Developments, 2021)
Artificial Neural Networks (ANN), a simple copy of the neurons in our brain, have been used for many years to bring people's problem-solving skills to computers. Although we have been able to run these networks faster with the help of developing technology, our need to run them better has created a challenging study area. Determining the hyper-parameters of the ANN has critical importance in this direction. In this study, an approach was inspired by Black Holes to determine the ANN hyperparameters. The Black Hole Algorithm (BHA), which is used as an optimization algorithm in the literature, is used for determining the hyperparameters of the ANN. The disadvantages of the BHA algorithm were identified and enhanced, a new approach called the Enhanced Black Hole Algorithm (EBHA) was proposed to the literature. Performance values ​​obtained by the test processes because the parameters selected with this algorithm are compared with other algorithms frequently used in the literature, it has been seen that the developed method achieves the most successful performance values.